Art of the Painter Nikolay I. Prokoshev - Goshchanskaya, Olga A. (Actual Problems of Theory and History of Art, 2014)
Nikolay I. Prokoshev (1904–1938), the artist of the 1920–1930s, graduated from the Art and Industrial College of Vyatka in 1925. His teacher was Michael A. Demidov. His studying at the VKhUTEMAS/VKhUTEIN in Moscow during 1926–1930 had a great impact on his art. The painting lessons of Konstantin N. Istomin particularly helped to develop Prokoshev’s colorist talent. Since that the artist worked on the color expressiveness and integrity of space and subject in painting. In his art the infl uence of both the French painting school and some Russian provincial openness is evident. He was suffering from tuberculosis since 1927, but was working hard in the 1930’s and made drawings and painting with increased attention to light refl ection. He created portraits, landscapes, still lifes, genre paintings “in the rooms”. He often painted his wife Lidiya N. Agalakova. Despite of his illness, Prokoshev was continually progressing and giving everything to the art.
Keywords: Nikolay Ivanovich Prokoshev; painter of 1920–1930’s generation; Vyatka; Mikhail A. Demidov; Konstantin N. Istomin; VKhUTEMAS/VKhUTEIN; Lidiya N. Agalakova